A comparison of the expression of known basement membrane components with the linear IgA disease antigens using the novel substrate cylindroma. - Wojnarowska, F; Allen, J; Collier, P; Leigh, I (1999)
Linear IgA disease (LAD) is characterized by IgA basement membrane zone autoantibodies. Immunofluorescence, immunoblotting and immunoelectron microscopy studies have established the complexity and heterogeneity of the target antigens. We have studied the expression of the LAD antigens by cylindroma, a benign epithelial tumour that secretes abundant basement membrane, using 57 LAD sera categorized by indirect immunofluorescence on intact and salt-split skin. The expression of known components of hemidesmosomes, the anchoring filaments, extracellular matrix and the anchoring fibrils could be differentiated and were compared with the expression of the LAD antigens. The results showed that the LAD sera bound to the cylindroma tumour in two distinctive patterns. Thirty-three sera were positive on cylindroma. Twenty-seven sera bound to the basement membrane around the tumour clusters and the islets within the clusters in a thin linear band that was occasionally discontinuous. This was similar to the pattern observed with antibodies to the hemidesmosome components, the alpha6beta4 integrin and the bullous pemphigoid antigens BP230 and BP180. This pattern was observed with sera that bound to the epidermal (11) and the dermal (3) aspects of split skin or were negative (11), and with one serum which bound only to intact skin. Seven sera, all binding to the dermal aspect of split skin, bound the tumour cluster basement membrane in a thick band that was identical in appearance to that seen with antibodies to collagen VII; however, binding to the islets was either identical to collagen VII or similar but differentiated with double staining. Some sera were negative on cylindroma. Using fluorescence overlay antigen mapping we demonstrated colocalization of some epidermal-associated LAD target antigens with known hemidesmosome proteins, and colocalization of some dermal-associated LAD target antigens with anchoring fibril components. The results using cylindroma as substrate suggest that LAD autoantibodies may react with three or more target antigens. We propose from the results of this study that the autoantibodies in LAD target multiple antigens associated with hemidesmosomes and anchoring fibrils.